Evaluasi Kinerja Keuangan dan Oprasional Usaha di Pondok Pesantren - Maulal Akmal, M Izzu; M. Masrukhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
operational sustainability. This study aims to evaluate the financial and operational performance of business enterprises at Imam Syafi'i Islamic Boarding School, Brebes, Central Java. A qualitative research method with a case study approach was employed. Data collection techniques included observations, in-depth interviews, and document analysis of financial and operational records. The findings indicate that the boarding school has managed various Sharia-based businesses, such as agriculture, livestock, and small-scale enterprises. Despite increased revenue from these businesses, challenges remain, including a lack of transparency in financial recording and limited human resources in business management. This study recommends improving Sharia-based financial recording systems, strengthening the capacity of business managers, and diversifying enterprises to enhance the economic sustainability of the boarding school. Keywords: Performance Evaluation, Islamic Boarding School Finance, Sharia Business, Economic Management, Case Study